Literature as an Agent of Change - Pierre-Robertson, Petronetta (Palgrave Macmillan, 2021)
A contextualization of the lived experiences of women is necessary for the prevention of domestic violence, a subcategory of violence against women. Unequal power relations, embedded in social relationships and institutions, have served to contribute to the perpetuation of violence against women. This chapter focuses on two areas in treating with the issue: positive media representation and literature. It presents a gendered analysis of select media accounts of the tragic outcome of domestic violence. Additionally, the chapter explores the role of literature as an agent of change in the prevention of violence against women. Through a creative work set in Trinidad, gendered assumptions and practices surrounding abuse, especially as it relates to toxic masculinity, are examined. Bystander intervention, which seeks to end the partnership of gender inequality and gender-based violence embedded as it were in social and cultural norms is highlighted.
Keywords: Domestic Violence; Media Representation; Intervention